Acupuncture Compared with Intramuscular Injection of Neostigmine for Postpartum Urinary Retention: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (14th May 2018) - Wang, Xiao-Mei; Gong, Jing; Li, Si-Cong; Han, Mei
Abstract : Objective . To compare the effectiveness and safety of acupuncture versus intramuscular injection of neostigmine. Methods . Databases including CNKI, VIP, WanFang, SinoMed, PubMed, Cochrane Library, and clinicaltrials.gov database were retrieved for relevant literature, with the retrieval deadline being November 2017. Two reviewers independently screened, selected, and extracted data and validated the results. The methodological quality was evaluated with the "Risk of Bias" tool, and the meta-analysis was performed by using the RevMan 5.3.5 software. Results . Totally 953 patients with postpartum urinary retention from 15 randomized controlled trials entered the meta-analysis. 12 articles compared the clinical cure rate of acupuncture alone versus intramuscular injection of neostigmine and found the cure rate in the acupuncture group was 2 times that in the neostigmine group (RR, 1.91; 95% CI: 1.66–2.19). 15 articles compared the clinical effectiveness rate of acupuncture alone with that of intramuscular injection of neostigmine and found the clinical effectiveness rate was 28% higher in the acupuncture group than in the neostigmine group (RR: 1.28; 95% CI: 1.16–1.42). No adverse event was reported in the acupuncture group. Conclusion . Acupuncture alone is more effective in treating postpartum urinary retention than intramuscular injection of neostigmine, with good safety profile. Therefore, it is a feasible and valuable technique in clinical settings.